Answer:
(f+g)(x) = -3x+5
Step-by-step explanation:
f(x)=x+8 and g(x)=-4x-3
(f+g)(x) = f(x) + g(x)
= x+8+-4x-3
= -3x+5
Answer: -12
Step-by-step explanation: To solve this problem, we can first start by rewriting the problem. When we add a negative, that's exactly the same thing as subtracting so we can make the problem easier to understand.
18 + (-30) → 18 - 30
To find the answer to this problem, let's first find out how many jumps it get's to 0 from 18. It would take 18 jumps and there is 12 jumps left over. Then, we would subtract 12 from 0 and we would get -12 as our answer. Therefore, 18 + (-30) = -12.
Answer: 135 nickels
Step-by-step explanation:
135 Nickels is $6.75 and 165 dimes is $16.50
That's 300 coins. $6.75 + $16.50 = $23.25
Answer:
Step-by-step explanation:
10x^3 + 35x^2 - 4x - 14
5x^2(2x + 7) - 2(2x + 7)
(5x^2 - 2)(2x + 7)